Differences in and relationship between digital access, use, connectivity, skill, engagement, and motivation: implications for digital inequality in online learning among first-generation and continuing-generation undergraduate students - Minas Michikyan; Kaveri Subrahmanyam; Pamela Regan; Miguel Ángel Cano; Linda G. Castillo; Audrey Harkness; Seth J. Schwartz (Discover Education)
Abstract Disruptions in education may exacerbate digital inequality among college student groups. This study examined differences in and relationships between digital access, use, and connectivity, digital skills and engagement, and academic motivation among first-generation (learners whose parents/guardians have no college education) and continuing-generation (learners whose parents/guardians have a college education) undergraduate students in the United States (N = 1224; M age = 21, 902 women, 56.8% first-generation status) in the context of COVID-19. Most first-generation and continuing-generation students reported unlimited and stable internet access at home. First-generation students reported less frequent access to fast and reliable internet and using multiple devices for online learning. First-generation and continuing-generation students reported similar levels of digital skills and engagement in online learning. Digital access and various digital skills and engagement were differentially associated with academic motivation. First-generation students reported greater academic motivation than their continuing-generation peers. Implications for reducing digital inequality for undergraduate students are discussed.